PENERAPAN METODE SIMPLEKS DALAM OPTIMALISASI KEUNTUNGAN HASIL PRODUKSI LEMON CINA DAN DAUN JERUK PURUT - Matheus Supriyanto Rumetna; Tirsa Ninia Lina; Atonur Dimara; Charles Sianturi; Chintia Metalmety; Kevin Lengkong; Mia Safitri; Nova Uniwaly; Wijayanto Wardhana Putra (LPPM Poltek ST Paul, 2020)
Mama Mia is a farmer in Sorong City, West Papua, which produces Chinese lemons and kaffir lime leaves for sale. In February-June, the price of Chinese lemons and kaffir lime leaves has decreased. In order for Mama Mia farmers to get optimum profit at the level of the month, good calculations need to be done, one of them using Linear Programming. This research is supported by technology in the form of POM-QM software for Windows version 5 to analyze the optimum profit from each production for 5 months. The purpose of this study was to analyze the maximum profit yield from the production of Chinese Lemon and Kaffir Lime Leaves using Linear Programming, the Simplex Method when production prices fell for 5 months. The result of the Simplex Method is very helpful for farmers like Mama Mia because it can analyze the maximum profit from the production of Chinese Lemon and kaffir lime leaves.